EFFECT OF COMBINATION PESTICIDE ON ACETYLCHOLINE ESTERASE ACTIVITY IN FRESHWATER FISH DANIO RERIO - RAJINI .A; REVATHY.K (International Journal of Pharma and Bio Sciences, 2015)
An aquatic system is mostly contaminated due to widely-used pesticides. The most popular classes of insecticides are organophosphates and synthetic pyrethroids. Chlorpyrifos and Cypermethrin are used around the world to control pest insects in agricultural, residential, and commercial buildings, although use in certain residential applications has been restricted in several countries. The effect of Chlorpyrifos 50% + Cypermethrin 5% EC on acetylcholine esterase activity in freshwater, Danio rerio was observed. AChE is an important enzyme that can be measured as an environmental bio-indicator. Group of fish were exposed to pesticide concentrations of 8 µg/L, 10 µg/L and 14 µg/L. Brain tissues were collected for analysis of the enzyme activity Acetylcholine Esterase (AChE). The inhibition of acetylcholinesterase activity increased with pesticide concentration and exposure period. Statistically significant change was calculated by ANOVA using SAS version 9.3.